Pengaruh Kecerdasan Emosional pada Kepuasan Kerja dan Prestasi Kerja dengan Mediasi Kemampuan Adaptasi Karyawan: Studi pada Kospin Jasa Regional Yogyakarta dan Jawa Tengah - Muhammad Khaidar Yasqi; Isthofaina Astuty (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to analyze the influence of emotional intelligence on job satisfaction and job performance, with employee adaptability as a mediator. The subjects were employees of Kospin Jasa Regional Office (Kospin Jasa) in Yogyakarta and Central Java. A sample of 178 respondents was selected using a census technique and a questionnaire was distributed using Google Forms. The analysis tool used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) software. The results of this study indicate that employee adaptability has a positive and significant effect on job satisfaction, employee adaptability has a positive and significant effect on job performance, emotional intelligence has a positive and significant effect on employee performance, emotional intelligence has a positive and significant effect on job satisfaction, and the influence of emotional intelligence on job performance has a positive and significant effect. Employee adaptability acts as a positive mediator in the influence of emotional intelligence on job satisfaction. Employee adaptability can be interpreted as a positive mediator in the influence of emotional intelligence on job performance.